An Error Analysis of English Voiceless Plosive Consonants /p/, /t/, and /k/ of Students at SMAN 11 Banda Aceh - Nurul Fajri; Abdul Gani Asyik (Universitas Serambi Mekkah, 2022)
This research was conducted based on the phenomenon happened in learning environment. The students have low ability in pronunciation. They got difficulty in pronouncing English words including plosive voiceless consonants sound. Therefore, this manuscript sheds lights on the errors produced in pronouncing plosive voiceless consonants sound. To find out the types of error and to find out the percentages of errors which students made in pronouncing plosive voiceless consonants /p/, /t/ and /k/ with aspirated and unaspirated. This research was conducted based on descriptive qualitative research design. The participants were 20 female tenth graders at SMAN 11 Banda Aceh, class of X IS 2. In collecting the data, a sheet containing 30 aspirated and unaspirated consonants /p/, /t/, and /k/ words was distributed, and then the students pronounced the words while their voice recorded. All recorded sound produced by participants checked thoroughly, they were played one by one. The transcriptions were used to find out how many errors produced. The researcher identified the words on transcription which produced an error, the researcher identified the student’s errors and after identifying the data, and finally the errors were classified. In this way, the researcher determined the types of error that belong to each type of error. Then, the errors that committed by the students put into the distribution table of errors to find out the number of errors each of the student committed. After classifying the data, the researcher calculated the students’ errors and made the total for each error by counting the errors to get the total of each error. The result of the research showed that there were three types of errors those are aspirated /h/ sounds as unaspirated, unaspirated sound as aspirated /h/ and all sounds unaspirated. The total of errors were 372 errors’ items which made by the students. The most common errors were all sounds unaspirated, which was 167 errors’ items or 44.9% made by the students, aspirated sounds as unaspirated was 131 items or 35.2% and unaspirated sounds as aspirated was 74 items of errors or 19.9%.